2015
DOI: 10.1111/bij.12583
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analysis reveals Holarctic homogeneity and a distinct Mediterranean lineage in the Golden eagle (Aquila chrysaetos)

Abstract: The Golden eagle (Aquila chrysaetos) is among the most widespread of the birds of prey, covering basically the whole Palaearctic from Europe and North Africa through Asia and Japan, to the North American continent. Only few studies have addressed the species’ genetic structure and the consequences of its demographic history so far, and none of them has covered larger areas of the distribution range. Our present study aims at closing this gap. Based on 283 samples (mostly feathers collected in the field or from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(82 citation statements)
references
References 47 publications
5
74
3
Order By: Relevance
“…Three mtDNA haplotypes were identified in the dataset from the 6 Alaskan eagles provided by Domenech and Sherrington; all three matched haplotypes identified in Sonsthagen et al [17] and two matched haplotypes from our dataset ([17]; Table 2). The haplotype identified in 5 Canadian eagles by Nebel et al [9] matched haplotype GOEA04 (Fig 1). Given our current sampling, haplotype GOEA05 appears to be specific to California while haplotype GOEA06 appears specific to Idaho (Table 2; Fig 1).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Three mtDNA haplotypes were identified in the dataset from the 6 Alaskan eagles provided by Domenech and Sherrington; all three matched haplotypes identified in Sonsthagen et al [17] and two matched haplotypes from our dataset ([17]; Table 2). The haplotype identified in 5 Canadian eagles by Nebel et al [9] matched haplotype GOEA04 (Fig 1). Given our current sampling, haplotype GOEA05 appears to be specific to California while haplotype GOEA06 appears specific to Idaho (Table 2; Fig 1).…”
Section: Resultsmentioning
confidence: 72%
“…Sequences were aligned by eye in Sequencher 4.7 (Gene Codes Corporation), and the number of haplotypes was determined using the filter redundant taxa option in MacClade 4.08 [38]. Golden eagle haplotypes from other studies in North America [9,17] were downloaded from Genbank (www.ncbi.nlm.nih.gov/genbank/). …”
Section: Methodsmentioning
confidence: 99%
“…Contemporary patterns of genetic diversity and population connectivity within species are influenced by demographic history, historical and present barriers to gene flow, and the species’ active and/or passive dispersal ability (Hewitt, 2000; Ellegren & Galtier, 2016). Thus, highly vagile generalist species with great active dispersal ability typically show little phylogeographic structure, sometimes even across their entire distribution range (e.g., Koblmüller et al, 2012; Statham et al, 2014; Nebel et al, 2015; Pfeiler & Markow, 2017). This is particularly true for pelagic fishes, which are usually highly mobile with their dispersal not restricted by physical barriers (e.g., Graves & McDowell, 2003; Theisen et al, 2008; García-Rodríguez et al, 2011), even though exceptions have been reported (e.g., Perrin & Borsa, 2001; Lu et al, 2006; Fauvelot & Borsa, 2011; Sebastian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For Holarctic species, patterns are diverse. Within birds of prey, surprisingly high genetic homogeneity across the Holarctic (with the exception of the Mediterranean region) has been found in Golden Eagles Aquila chrysaetos (Nebel et al., ), whereas high intercontinental divergence of haplogroups has been observed for several other bird species (Johnsen et al., ; Zink, Rohwer, Drovetski, Blackwell‐Rago, & Farrell, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…We used two mitochondrial (mt) DNA markers: partial sequences of the control region ( CR ) and the cytochrome b ( cytb ) gene. These genomic regions have proved to be useful in numerous studies on differentiation in birds of prey (Lerner et al., ; Nebel et al., and references therein) and allowed us to include previously published sequences and compare results. Moreover, they have been shown to resolve both recent and deeper divergences (Lerner et al., ).…”
Section: Introductionmentioning
confidence: 99%